2014
DOI: 10.1063/1.4875808
|View full text |Cite
|
Sign up to set email alerts
|

Fast growth of ultrananocrystalline diamond films by bias-enhanced nucleation and growth process in CH4/Ar plasma

Abstract: This letter describes the fast growth of ultrananocrystalline diamond (UNCD) films by biasenhanced nucleation and growth process in CH 4 /Ar plasma. The UNCD grains were formed at the beginning of the film's growth without the necessity of forming the amorphous carbon interlayer, reaching a thickness of $380 nm in 10 min. Transmission electron microscopic investigations revealed that the application of bias voltage induced the formation of graphitic phase both in the interior and at the interface regions of UN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…There is no H (or H þ ) species present in CH 4 /Ar plasma. It should be noted that previous studies observed that for the UNCD films grown without bias voltage, an a-C phase was formed preferentially, 50,51 resulting in an amorphous carbon (a-C) layer that is schematically illustrated in Fig. 10(a).…”
Section: Discussionmentioning
confidence: 97%
“…There is no H (or H þ ) species present in CH 4 /Ar plasma. It should be noted that previous studies observed that for the UNCD films grown without bias voltage, an a-C phase was formed preferentially, 50,51 resulting in an amorphous carbon (a-C) layer that is schematically illustrated in Fig. 10(a).…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the enhancing factor, recently, a theoretical study anticipated values of 3.7, 1.9 and 1.7 for the diamond (100)-2x1 surface, (111) and (110) surfaces (all terminated by hydrogen), respectively [14], supporting the experimentally observed values for single crystal diamond [10]. It is worth to point out that for NCD films, the enhancing factor of nitrogen addition on the growth rate can be considered only as an average effect from all {100}, {110} and {111} contributing surfaces in the film.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 62%
“…NCD films have been produced using Ar/CH 4 feeding gases [6] or through the introduction of nitrogen additive into CH 4 /H 2 gas mixtures [5,[7][8][9]. For example, it was recently reported that a high growth rate 2.4 µm/h was achieved for ultrananocrystalline diamond films grown by bias enhanced nucleation and growth process using CH 4 /Ar plasma [10]. It has been shown that the amount of nitrogen added into the gas phase has significant influence on the electrical properties of the produced nitrogen incorporated NCD films [11].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the presence of sufficient amount of CH species in the plasma is necessary for retaining the small size of the diamond grains, 41 as the CH species can encapsulate the newly nucleated diamond clusters, thereby preventing them from growing bigger. Moreover, in previous studies for bias-enhanced growth of ultrananocrystalline diamond (UNCD) films, [42][43][44] it is observed that the larger C 2 abundance in the plasma leads to a higher growth rate, whereas the increase in CH concentration in the plasma induces the formation of a nanographitic phase in the films.…”
Section: Discussionmentioning
confidence: 94%